MODEL PENGEMBANGAN PERMAINAN JUMPGOSO DALAM PENJASORKES PADA SISWA KELAS III SD NEGERI SUKODADI 2 KECAMATAN BANDONGAN KABUPATEN MAGELANG TAHUN 2013/2014 (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to produce a product development model in Penjasorkes jumpgoso games at third grade students of SD Nageri Sukodadi 2 Bandongan District of Magelang regency. The method used in this research is the development of Borg & Gall. The average of the results of validation expert on small -scale trials obtained a percentage of 81.33% (excellent). The average yield on a student questionnaire small scale trials obtained a percentage of 84.21% (excellent). From the average yield on the expert validation field trials obtained percentage of 86.66% (excellent). The average yield on the student questionnaire field trials obtained a percentage of 88.87% (excellent). From the above data it can be concluded that the model of development jumpgoso game can be used as an alternative learning model for students of class III Penjasorkes Elementary School Sukodadi 2 Bandongan District of Magelang regency.